A Study to Assess the Knowledge, Attitude, and Experience Regarding Diabetes and Its Related Conditions among Dental Practitioners - Gupte, Rishabh; Shetty, Manoj (Journal of Health and Allied Sciences NU, 2024)
Diabetes is a chronic condition which leads to dysfunction of multiple systems and requires a multidisciplinary approach for its effective management. A survey was performed on 308 dental professionals to record their experiences regarding the awareness of oral complications as well as their means of effective communication with medical practitioners for better holistic diabetic care. Additionally, they were also asked knowledge-based questions and ones related to diagnostic criteria and data collection and interpretation. Roadblocks for the effective care with two-way communication with medical doctors were also recorded with possible solutions along with protocols for effective screening and assessment of current burden of disease, dealing with diabetic emergencies and reduction of morbidity for the patients to efficiently treat the diabetic patient in a dental practice.
Keywords: diabetes; dentistry; holistic treatment; communication; complications of diabetes